Assessing the consistency of in-stream tidal energy development policy in Nova Scotia, Canada. (March 2020) - Carlson, Jordan Thomas; Adams, Michelle
Abstract: The provincial government of Nova Scotia, Canada, has provided numerous incentives for developing in-stream tidal energy projects since 2009. These incentives include co-operatively funding the development of the Fundy Ocean Research Centre for Energy with the Canadian federal government and industry partners, extensive funding of environmental impacts monitoring research for tidal energy projects, and offering direct financial incentives for tidal power produced and sold to the grid via feed-in tariffs. However, the provincial government has not treated all scales and types of tidal energy projects equally. Until recently, ambitious targets for hundreds of MW of tidal development by 2020–2025 led to tidal support policies focusing on large, utility-scale projects, with little evidence the tidal energy sector was prepared to pursue such projects in Nova Scotia or elsewhere. Some support was offered to smaller-scale, community-oriented tidal energy projects, but the rules and regulations for such projects were repeatedly changed (and sometimes revoked) between 2012 and 2018. Since the provincial legislature passed the revised Marine Renewable-electricity Act of 2018, a potentially more coherent and consistent tidal energy policy consensus appears to be forming in the province. This paper provides a review of the policies introduced, projects approved and canceled, and sectoral outlook for tidal energy development in Nova Scotia for the period 2009–2018.